Using Zebrafish in Preclinical Drug Studies: Challenges and Opportunities - A. V. Kalueff; M. M. Kotova; A. N. Ikrin; T. O. Kolesnikova (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2023)
Scientific relevance. Since fiscal and regulatory constraints substantially limit bioscreening in rodent models, a wider implementation of additional alternative models in preclinical studies of medicines is gaining momentum. These alternative models include aquatic vertebrates, such as zebrafish (Danio rerio).Aim. The study aimed to examine zebrafish models in terms of their performance in preclinical studies, their current uses, the challenges and opportunities in the field, and strategic directions for the development of preclinical testing in zebrafish.Discussion. Here, the authors summarise the key zebrafish tests that are currently used to assess a wide range of small molecules for their general and endocrine toxicity and effects on the survival of embryos and larvae. The review discusses the strengths and weaknesses of zebrafish models for preclinical testing of neurotropic agents. Additionally, the authors overview various methodological approaches to improving zebrafish toxicity testing. Overall, the use of zebrafish models is gradually becoming internationally established for laboratory testing of small molecules.Conclusions. A wider implementation of zebrafish models in pharmaceutical research and preclinical testing as an additional alternative to rodents, particularly in Russia, may significantly accelerate the development of novel medicinal products and foster a more comprehensive and adequate assessment of the biological risks associated with chemical substances.